Q: For real numbers a,b show the following by stating the properties used:      i) (-a)b = a(-b) = -ab         ii) (-a)(-b) = ab

in Algebra 1 Answers by Level 1 User (160 points)

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

Let c be a real number, then the associative rule says that (a*b)*c=a*(b*c); the commutative rule says that a*b=b*a, a*c=c*a and b*c=c*b. a*c=a*-1=c*a=-1*a=-a and b*c=c*b=-1*b=-b, when c=-1.

(-a)(b)=(ca)b=(ac)b=a(cb)=a(-b).

Let x=c*c=c^2=(-1)^2=1. (ca)(cb)=(ac)(cb)=a(c*c)b by the associative rule=a(x)b=(xa)b=x(ab)=1(ab)=ab.

by Top Rated User (736k points)

Related questions

1 answer
asked Jun 21, 2017 in Other Math Topics by syed4all Level 1 User (160 points) | 128 views
1 answer
asked Sep 20, 2013 in Other Math Topics by anonymous | 122 views
0 answers
asked Apr 9, 2014 in Geometry Answers by xoxamberxox Level 1 User (340 points) | 184 views
1 answer
asked Nov 10, 2013 in Word Problem Answers by becci | 121 views
0 answers
asked May 11, 2013 in Geometry Answers by anonymous | 130 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
84,759 questions
89,807 answers
2,029 comments
29,559 users